2021
DOI: 10.1001/jamaoncol.2020.6583
|View full text |Cite
|
Sign up to set email alerts
|

Maternally Orphaned Children and Intergenerational Concerns Associated With Breast Cancer Deaths Among Women in Sub-Saharan Africa

Abstract: IMPORTANCE Low breast cancer survival in sub-Saharan Africa's young population increases the likelihood that breast cancer deaths result in maternal orphans, ie, children (<18 years) losing their mother.OBJECTIVE To estimate the number of maternal orphans and their ages for every 100 breast cancer deaths in sub-Saharan African settings during 2014-2019 and to describe family concerns about the orphaned children.DESIGN, SETTING, AND PARTICIPANTS Deaths occurring between September 1, 2014, and July 1, 2019, in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 14 publications
1
29
0
Order By: Relevance
“…Therefore, we could speculate that the impact of breast cancer on productivity and family in low-middle and low SDI is enormous (28). A cohort in sub-Saharan Africa detects that the number of maternal orphans due to breast cancer exceeds the number of breast cancer deaths among females (29). To minimize the intergenerational effects of breast cancer deaths in sub-Saharan Africa, it is necessary to deliver adequate rehabilitation programs at crucial times in breast cancer survivors' recovery.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we could speculate that the impact of breast cancer on productivity and family in low-middle and low SDI is enormous (28). A cohort in sub-Saharan Africa detects that the number of maternal orphans due to breast cancer exceeds the number of breast cancer deaths among females (29). To minimize the intergenerational effects of breast cancer deaths in sub-Saharan Africa, it is necessary to deliver adequate rehabilitation programs at crucial times in breast cancer survivors' recovery.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that the majority of breast cancer deaths occur among women in the reproductive age group. This implies that, in addition to attention on pregnancy- or childbirth-related deaths, awareness needs to be raised regarding breast cancer affecting women in this age group where they are responsible for families and children [ 16 ]. We found that breast cancer is the second leading cause of death from neoplasms in women and among the top five causes of death from NCD.…”
Section: Discussionmentioning
confidence: 99%
“…A standard four-digit VA questionnaire on signs and symptoms, duration of illness, and health service visits was used for data collection [ 16 ]. Few modifications to the survey were made with input from an expert medical panel to include detailed breast cancer symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…In another study of women conducted across four African countries (Namibia, Nigeria, Uganda and Zambia), it was estimated that for every 100 deaths from breast cancer (women younger than 50 years), 210 new orphans were created with the number increasing to 247 for Zambia alone. 35 The study prospectively followed Review 1541 women and had 91% of deaths reported by next of kin who were asked how the death affected the family. The impact of the woman's death included emotional, physical and financial distress.…”
Section: The Negative Cascade Of Uncontrolled Cancer In African Womenmentioning
confidence: 99%